Uniqueness of Solutions of Some Nonlocal Boundary-Value Problems for Operator-Differential Equations on a Finite Segment - Radzievskii, G. V. (Ukrains’kyi Matematychnyi Zhurnal, 2003)
For the equation L 0 x(t) + L 1 x (1)(t) + ... + L n x (n)(t) = 0, where L k, k = 0, 1, ... , n, are operators acting in a Banach space, we formulate conditions under which a solution x(t) that satisfies some nonlocal homogeneous boundary conditions is equal to zero.